2021
DOI: 10.1016/j.envres.2020.110443
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented environmental and energy impacts and challenges of COVID-19 pandemic

Abstract: The rapid transmission tendency, severity, and wide geographical spread of newly emerged novel coronavirus (SARS-CoV-2) in different environmental matrices, including water, air, and soil, has posed severe health, environmental, energy, and economic challenges worldwide. Despite the severe health effects, unprecedented improvements in air quality in many countries due to emergency measures, and public behavior changes have been reported. SARS-CoV-2 has been detected in air and sewage samples in several studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 53 publications
0
53
0
Order By: Relevance
“…Considering the first question, how can HVAC designs adapt to both the normal situation and pandemic situation simultaneously? Three key issues have come to light: a) conventional HVAC systems have little ability to filter and kill viruses as revealed by Siddique and others [135] , and to reduce the risk of SARS-CoV-2 spreading and cross infection during the pandemic; b) current HVAC systems are designed according to previous guidelines, and thus may not meet requirements during the pandemic, and fail to provide enough ventilation rate to dilute indoor air pollutant concentration; and c) HVAC system capacity may be insufficient to undertake the full heating and cooling load as presented in Ref. 50 with disabling air recirculation recommended to prevent the risk of cross infection.…”
Section: Future Challenges and Innovations Of Hvac Systemsmentioning
confidence: 99%
“…Considering the first question, how can HVAC designs adapt to both the normal situation and pandemic situation simultaneously? Three key issues have come to light: a) conventional HVAC systems have little ability to filter and kill viruses as revealed by Siddique and others [135] , and to reduce the risk of SARS-CoV-2 spreading and cross infection during the pandemic; b) current HVAC systems are designed according to previous guidelines, and thus may not meet requirements during the pandemic, and fail to provide enough ventilation rate to dilute indoor air pollutant concentration; and c) HVAC system capacity may be insufficient to undertake the full heating and cooling load as presented in Ref. 50 with disabling air recirculation recommended to prevent the risk of cross infection.…”
Section: Future Challenges and Innovations Of Hvac Systemsmentioning
confidence: 99%
“…1 ). All the environmental compartments have benefited of the restrictive measures adopted to contain the infection ( Siddique et al, 2021 ).
Fig.
…”
Section: Impact Of Covid-19 Pandemic On the Environment And Biotamentioning
confidence: 99%
“…One of the major challenges faced by land freight is increased manufactured goods that have created challenges for the land travelers for dealing with freight issues based on the arguments of Jain and Sharma (2020). It has been observed that the capacity for ocean transport has decreased, which has also increased the pressure on the land freight and badly affected the timely services for logistics and transportation, as referred to in the study of Siddique et al (2021). The significance of the COVID-19 pandemic has created a major shift from physical buying to online buying that is also one of the significant challenges in creating the increased pressure on the land freight, as referred to in the study of Benmarhnia (2020).…”
Section: Impact Of Covid-19 On Transportation and Logisticsmentioning
confidence: 99%